PENYUSUNAN KEBIJAKAN TERINTEGRASI DALAM INDUSTRI PARIWISATA DENGAN KONSEP PENTAHELIX STRATEGY - I Putu Danny Pramana Putra; Made Natalia Supadmi; Lis Julianti; Ni Putu Noni Suharyanti; Agustina Ni Made Ayu Darma Pratiwi (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
The Covid-19 pandemic has had a significant impact on the economy in Bali. Efforts to formulate a strategic and integrative policy in the tourism sector to accelerate the post-Covid-19 economic recovery can be done by implementing the Pentahelix Strategy in the development of the tourism industry. This strategy collaborates with Academia-Business-Community-Government and Media, which are oriented towards meeting the needs of the tourism industry based on local wisdom. The general objective of this study is to determine how the implementation of tourism policy in Denpasar City post-Covid-19 pandemic is conducted, as well as to identify the synergies of the Pentahelix Strategy in formulating tourism policies as an effort to support economic recovery in Denpasar City. This research reflects a descriptive-analytical study, a type of research that is not only limited to description but also to efforts to study the characteristics of problem-solving cases in tourism investment. The research method used is qualitative research, often referred to as a naturalistic research method because the research is conducted in natural settings. It is also known as an ethnographic method because it was originally used more in cultural anthropology research. This method is called qualitative because the collected data and analysis are more qualitative in nature.